Pengaruh Smartphone Addiction terhadap Perilaku Seks Pranikah dengan Self Control Sebagai Variabel Mediasi pada Siswa SMA - Fatimah Triyani; Suryani Hardjo; Siti Aisyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
A person's attitude toward sexual behavior is closely related to their level of knowledge, so it is very important to know how teenagers feel about sexual behavior. Teenagers' attitudes toward premarital sex can be influenced by many things, including knowledge, culture, mass media, personal experiences, educational institutions, religious institutions, and individual emotions. This study aims to analyze the influence of smartphone addiction on premarital sex through self-control as a mediator. The sample used was 177 students with a purposive sampling technique. The data collection methods used were the smartphone addiction scale, the premarital sex behavior scale, and the self-control scale. The data analysis technique used in this study was Structural Equation Model (SEM). The results of this study indicate that there is a significant negative influence between smartphone addiction and self-control with a p-value of 0.001 < 0.05 and a t-count of 3.340 > 1.96 (Table 4.24). There is a significant negative influence between self-control and premarital sex behavior among high school students in Stabat District, based on a p-value of 0.000 < 0.05 and a t-value of 14.309 > 1.96. There is no significant direct effect between smartphone addiction and premarital sex behavior among high school students based on a p-value of 0.107 > 0.05 and a t-value of 1.615 < 1.96. Self-control plays a significant mediating role between smartphone addiction and premarital sex behavior among high school students, with a Sobel Test t-value of 3.59 > 1.96 and a two-tailed p-value of 0.000 < 0.05.